CSF TACI and BAFF levels in patients with primary CNS lymphoma as novel diagnostic biomarkers. Issue 12 (19th October 2018) - Mizutani, Hironori; Nakane, Shunya; Ikeda, Tokunori; Nakamura, Hideo; Takamatsu, Koutaro; Makino, Keishi; Tawara, Nozomu; Mukaino, Akihiro; Watari, Mari; Matsui, Hirotaka; Mukasa, Akitake; Ando, Yukio
Abstract: We used an enzyme‐linked immunosorbent assay to measure pretreatment B cell‐activating factor belonging to the tumour necrosis factor family (BAFF) and transmembrane activator and CAML‐interactor (TACI) levels in CSF and serum collected from patients with primary central nervous system lymphoma (PCNSL) and control groups. The decision tree analysis of CSF TACI and BAFF levels for patients with a PCNSL diagnosis showed 100% sensitivity and 100% specificity when we attempted to differentiate PCNSL from glioblastoma and CNS inflammatory diseases. The combination of CSF TACI and BAFF levels may thus be a novel and useful diagnostic biomarker of PCNSL.